Peran PKK Kota Medan terhadap Pencegahan KDRT Perspektif UU Nomor 23 Tahun 2004 - Mulyana, Andista Anang; Irwan, Irwan (SIGn Jurnal Hukum, 2025)
The high incidence of domestic violence in Medan City indicates a gap between the legal protection framework and the implementation of prevention at the grassroots level. This study aims to analyze the form and implementation of the role of the Family Welfare Empowerment Mobilization Team in domestic violence prevention according to Law Number 23 of 2004 and to identify the determining factors that influence its effectiveness. This empirical legal research utilizes a qualitative approach with a case study design focusing on the Medan City Family Welfare Empowerment Mobilization Team. Data were collected through in-depth interviews with key informants and document studies and analyzed using an interactive analysis model. The findings indicate that the role of Family Welfare Empowerment is paradoxical: while aligned with the preventive spirit of Law Number 23 of 2004, its implementation in the field tends to be based on the maintenance of social harmony rather than the protection of victims’ juridical rights. The effectiveness of this role is determined by a dialectic between its social capital and grassroots network as primary supporting factors, which confront the hegemony of patriarchal culture, limitations in authority, and the complexity of victims’ dilemmas as dominant hindering factors. It is concluded that Family Welfare Empowerment is a vital yet limited preventive partner whose potential can only be optimized through systemic policy support to strengthen its cadres’ legal and intervention capacities.